2012
DOI: 10.1017/s0025315412000215
|View full text |Cite
|
Sign up to set email alerts
|

Accommodation of the sex-ratio in eastern oysters Crassostrea virginica to variation in growth and mortality across the estuarine salinity gradient

Abstract: Protandric oysters generate a relatively uniform reproductive potential over a wide range of environmental conditions that impose variations in growth rate and life span. Sex-at-length keys applied to survey data show that the female fraction routinely fell between 0.4 and 0.5, regardless of location in the salinity gradient. About 70% of population biomass is female over the same salinity range. Due to the necessary local modulation of the rate of male-to-female conversion to limit the influence of varying gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 80 publications
0
29
1
Order By: Relevance
“…In each generation, a protandric male is given the chance to convert to a functional female. A conversion probability was obtained from empirical data from Delaware Bay (Powell et al ., ) using age–length relationships developed by Kraeuter et al . ().…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In each generation, a protandric male is given the chance to convert to a functional female. A conversion probability was obtained from empirical data from Delaware Bay (Powell et al ., ) using age–length relationships developed by Kraeuter et al . ().…”
Section: Methodsmentioning
confidence: 99%
“…Powell et al . () found that the relationship between the fraction of the population that is female, Ff , and age could be modelled as a Gompertz curve: Ff=αeβeγAgewhere α and β are population‐specific parameters (Table ). The first derivative of Equation gives the rate at which any animal can change from male to female ( Df ) as: Df=italicdFfitalicdAge=αβγe()()γitalicAge+()βeγAgewhere γ is a population‐specific parameter (Table ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One obvious option would be an increasing maleness in the population with declining adult length, if that decline was a function of declining longevity or reduced growth rate. Powell et al (2013) noted that the sex change was a complicated function of both age and length, modulated by within-population processes. The association of increasing maleness with decreasing length is dramatically apparent in oysters from the Gulf of Mexico over the 1995 to 2010 time series and also is present in oysters taken from the Southern Mid-Atlantic.…”
Section: The Major Taxa and Continental Trends In Physiological Indicesmentioning
confidence: 99%